2019
DOI: 10.1021/acs.est.9b00592
|View full text |Cite
|
Sign up to set email alerts
|

Methylated Thioarsenates and Monothioarsenate Differ in Uptake, Transformation, and Contribution to Total Arsenic Translocation in Rice Plants

Abstract: Methylated and inorganic thioarsenates have recently been reported from paddy fields besides the better-known oxyarsenates. Methylated thioarsenates are highly toxic for humans, yet their uptake, transformation, and translocation in rice plants is unknown. Here, hydroponic experiments with 20 day old rice plants showed that monomethylmonothioarsenate (MMMTA), dimethylmonothioarsenate (DMMTA), and monothioarsenate (MTA) were taken up by rice roots and could be detected in the xylem. Total arsenic (As) transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 62 publications
6
58
1
Order By: Relevance
“…Method C used the same enzymatic extraction as method B with the exception that the saline solution was replaced by a phosphate buffer solution (PBS, 2 mmol L –1 of NaH 2 PO 4 + 0.2 mmol L –1 of Na 2 -EDTA, pH 2) to reduce the salt load and because the stability of MTA and DMMTA in PBS had previously been confirmed. For chromatographic separation, a method that had previously been developed to separate inorganic and methylated thioarsenates in aqueous samples was applied, using an AG/AS16 IonPac column (Dionex; 2.5–100 mmol L –1 of NaOH + 2.4% methanol eluent, gradient elution, a flow rate of 1.2 mL·min –1 , and 50 μL injection volume).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Method C used the same enzymatic extraction as method B with the exception that the saline solution was replaced by a phosphate buffer solution (PBS, 2 mmol L –1 of NaH 2 PO 4 + 0.2 mmol L –1 of Na 2 -EDTA, pH 2) to reduce the salt load and because the stability of MTA and DMMTA in PBS had previously been confirmed. For chromatographic separation, a method that had previously been developed to separate inorganic and methylated thioarsenates in aqueous samples was applied, using an AG/AS16 IonPac column (Dionex; 2.5–100 mmol L –1 of NaOH + 2.4% methanol eluent, gradient elution, a flow rate of 1.2 mL·min –1 , and 50 μL injection volume).…”
Section: Methodsmentioning
confidence: 99%
“…8 Uptake of thioarsenates by rice plants has been shown before. 11,12 The presence of MTA in rice roots and shoots has been confirmed by direct analytical evidence, 11 and hydroponic experiments have demonstrated that MTA, 11 MMMTA, 12 and DMMTA 12 can reach the xylem of rice plants. In rice grains, As speciation is dominated by iAs and DMA.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice plants can take up monothioarsenate and transport it in the xylem (Kerl et al, 2018). Dimethylmonothioarsenate has also been detected in rice grains and can account for up to 20% of the total As in the enzymatic extracts of commercial rice samples (Ackerman et al, 2005;Kerl et al, 2019). A hydroponic study found that rice roots accumulated about 10 time more dimethylmonothioarsenate than DMAs when plants were supplied with the same concentration of the two As species, indicating a high uptake and/or sequestration of dimethylmonothioarsenate in rice roots (Kerl et al, 2019).…”
Section: Transporters For Thioarsenates In Plantsmentioning
confidence: 99%
“…Outside the plant, MMMTA could be dethiolated to MMAs(Ⅴ) due to abiotic oxidation, but DMMTA was not oxidized abiotically. DMMTA had the highest potential to promote total As accumulation either as DMAs(Ⅴ) or potentially as DMMTA [12]. The concentration of arsenic in the human body is determined mainly by the arsenic concentration in drinking water and the seafood consumption in the diet.…”
Section: Introductionmentioning
confidence: 99%